Nizhny Novgorod Muslim Tatars in the regional dimension (methodological aspect) - Сенюткина Ольга Николаевна (Историческая этнология, 2024)
The author of the article explores methodological approaches to the study of Nizhny Novgorod Muslim Tatars, which found application in the works of predecessors or those that are still awaiting testing. In this case, a microsection of the Nizhny Novgorod sociocultural space is used. Particular attention in the article is drawn to the conceptual apparatus of describing the history of the Mishars, identifying the specific features of the Mishar subethnic group of the Tatar nation and the role of the state in creating turning points in the history of this community. The author shows that one of the research angles for studying the history of Muslims (including the Russian Tatar-Muslim world) may be believers’ place of residence, their localisation. The use of the regional dimension when writing the history of Russia’s Tatars is completely justified, if for no other reason than that specific features have historically developed in the process of development of individual subethnic groups of the Tatar people (Siberian Tatars, Crimean Tatars, etc.). Using the example of the history of the Nizhny Novgorod Region Tatars, the author proves the advantages of using such a principle as interdisciplinarity, considering it possible to apply individual elements of certain methodologies to understanding ethnicity in the optics of historical ethnology. The author draws attention to another important research problem – the significance of regional specifics, both in studying the structure and self-awareness of the autochthonous peoples of Russia in their subethnic context, and, related to this, the regional specifics of a multi-ethnic and multi-confessional state, that is the Russian Federation. The materials of the article allow us to speak about the relevance of the topic chosen by the author, since the overall ethnic picture of Russia consists of individual regional “strokes”.